Psychology & mental health - Piotrowski, Nancy A. (Pasadena, Calif. : Salem Press, 2010)
This comprehensive five-volume set covers notable theories, people, social issues, life stages, the physiology and anatomy of the nervous system, and various mental illnesses or conditions --from publisher description.
v.1 Ability tests--Community psychology -- v.2 Comorbidity--Health psychology -- v.3 Hearing--Parental alienation syndrome -- v.4 Parenting styles--Sleep -- v.5 Sleep apnea--Zombardo, Philip ; Appendixes.
Includes bibliographical references and index.
Keywords: Psychology, Applied; Medicine and psychology